The Soul in Ascent : Bonaventure on Poverty, Prayer and Union with God - Johnson, Timothy J. (Book collections on Project MUSE., 2012)
First published by Franciscan press in 2000, Dr. Timothy J Johnson's The Soul in Ascent: Bonaventure on Poverty, Prayer and Union with God has offered a thorough textual study of the importance of prayer in Bonaventure's theology and life. This new edition is updated to include Johnson's most recent work on Bonaventure's Sunday Sermons sourced from his work, The Sunday Sermons of St. Bonaventure--Bonaventure Texts in Translation Series. This new edition is a must-read book for anyone interested in Franciscan spirituality and theology.